Decision Drivers for Optimal Fishing Vessel Design in Maluku Waters using Analytic Hierarchy Process - Billy J Camerling; Richard Benny Luhulima (Department of Naval Architecture - Diponegoro University, 2026)
The selection of optimal fishing vessel hull configuration for operations in Maluku Waters requires systematic evaluation of multiple interrelated decision criteria. This research applies the Analytic Hierarchy Process (AHP) methodology to evaluate three distinct hull configurations—monohull, catamaran, and trimaran—based on three primary decision drivers: resistance, fuel efficiency, and crew operational requirements. Using a hierarchical decomposition approach with pairwise comparison matrices and consistency testing, this study establishes weighted priority rankings for hull configuration selection. Hydrodynamic analysis reveals that trimaran vessels exhibit 9.4% lower total resistance compared to monohull vessels (98.5 kN vs. 108.0 kN at 12 knots), with corresponding fuel consumption reductions of 9.7% (4.86 tons vs. 5.38 tons). Catamaran configurations demonstrate intermediate performance with 6.6% lower resistance than monohull vessels. AHP results indicate that resistance (weight: 0.45) and fuel efficiency (weight: 0.38) emerge as the dominant decision criteria, while crew comfort and operational factors (weight: 0.17) represent secondary considerations. The synthesized AHP prioritization method provides decision-makers with quantitative frameworks for vessel selection aligned with Maluku Waters operational requirements. This research contributes a systematic multi-criteria methodology applicable to regional fishing fleet optimization and vessel procurement decisions.